22. CHARACTERISTICS OF USING THE SCALE TO ASSESS ANOREXIA IN CHILDREN FROM 6 MONTHS TO 5 YEARS OLD WHO OUTPATIENT AT THAI NGUYEN GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aimed to describe the status of the incidence of anorexia in children from 6 months to years old at Thai Nguyen General Hospital.Subjects and methods: Cross-sectional descriptive study on 265 children and caregivers of children from 6 months to 5 years old who visited Thai Nguyen Central Hospital from March 2024 to November 2024 participated in direct interviews based on the scale to assess the status of anorexia in children.Results: 265 incident cases of anorexia were reported over the 1-month surveillance period and assessed as eligible for inclusion. The majority were boy (58.1%), mean age was 25.43 months (±16.95), more common in the 13-24 months group (31.7%), 6-12 months group (25.3%). The rate of anorexia in the study was 44.9%; In which, the characteristics of children's meals: holding food for a relatively long time (36.2%); Eating half of the portion then holding food for a very long time (34.0%); Meal time were from 45-60 minutes (13.6%); and 34.0% of children eat relatively little; Characteristics of children's eating behavior: Occasionally having opposing behaviors when eating, accounting for 51.3%; occasionally having avoidance behaviors when eating (51.3%).Conclusion: Estimates of the incidence of anorexia in children from 6 months to 5 years old in our study was 44.9%.
Keywords: Anorexia; children under 5 years old; anorexia scale.